Solid waste management and environmental sustainability in alto Piura, Peru - Velásquez-Hidalgo, Oswaldo (2025)
The objective of this research was to analyse the relationship between solid waste management and environmental sustainability in Alto Piura, Perú. Solid waste management in rural areas of northern Peru presents structural gaps that limit environmental sustainability and foster informal disposal practices that affect environmental quality in the Hualtacal sub-basin, where the district’s dumping site is located. The study employed a quantitative approach, based on the application of surveys during September and October 2025; the sample consisted of 200 residents, selected using statistical criteria of proportional allocation, achieving a 95% confidence level and a ±5% margin of error. The questionnaire was subjected to expert review to ensure its relevance and clarity, and internal consistency was evaluated using Cronbach’s alpha coefficient. The results show that 60% of the population consider the waste collection service inadequate and three-quarters perceive deficiencies in municipal infrastructure and equipment. The study also reveals low effectiveness of environmental communication strategies and limited knowledge of regulations and municipal plans (such as PIGARS). There is a clear absence of environmental education and recycling programmes; 80% of respondents state that citizen participation is very low, evidencing a weak connection between institutional strategies and community engagement. In addition, 160 respondents express their disagreement with the final disposal of waste in the Hualtacal ravine and perceive negative effects on water, air, soil and biodiversity. The data reveal a municipal service that operates with structural fragility and without sufficient capacity to prevent environmental impacts. The lack of communication, education and participation not only hinders the adoption of good practices, but also prevents the consolidation of robust environmental governance. The continued use of the Hualtacal ravine as a disposal site confirms the absence of formal alternatives and highlights the role of insufficient infrastructure in sustaining inadequate practices. Taken together, these elements explain why current management contributes to environmental degradation and limits progress towards a sustainable model.   TRANSLATE with x English Arabic Hebrew Polish Bulgarian Hindi Portuguese Catalan Hmong Daw Romanian Chinese Simplified Hungarian Russian Chinese Traditional Indonesian Slovak Czech Italian Slovenian Danish Japanese Spanish Dutch Klingon Swedish English Korean Thai Estonian Latvian Turkish Finnish Lithuanian Ukrainian French Malay Urdu German Maltese Vietnamese Greek Norwegian Welsh Haitian Creole Persian     TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster Portal Back